PENGARUH UKURAN PERUSAHAAN, LEVERAGE, ASIMETRI INFORMASI DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2016) - Rizke Maulina; Nasrizal Nasrizal; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to know the affect of size of company, leverage, information asymmetry, and bonus compensation to earnings management of manufacturing company listed in Indonesia Stock Exchange (BEI) year 2015-2016. The earnings management as the dependent variable in this study is measured by the proxy of discretionary accruals. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2015-2016 as many as 143 companies. The sample is chosen by purposive sampling method. Through the criteria applied, selected samples of 87 manufacturing companies. The analytical method used is multiple linear regression analysis with SPSS application. After data processing, the result of the research shows that size of company and bonus compensation affect earnings management. But leverage and information asymmetry does not have an affect to earnings management. The adjusted R Square of 0,277 means that the contribution of independent variables (size of company, leverage, information asymmetry, and bonus compensation) to the dependent variable (earnings management) is 27,7% while the remaining 72,3% influenced by other variables not included in this study.Keywords : Earnings Management, Size Of Company, Leverage, Information Asymmetry, Bonus Compensation